A new factor for fabrication technologies evaluation for silicon nanowire transistors - Yasir Hashim; Mohammed Nazmus Shakib (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper reviews the fabrication technologies of silicon nanowire transistors (SiNWTs) and rapidly development in this area, as this paper presents various types of SiNWT structures, development of SiNWT properties and different applications until nowadays.  This research provides a good comparison among fabrication technologies of SiNWTs depending on a new factor DIF, this factor depends on the size of channel and power consumption in channel. As a result of this comparison, the best technology to use in the future to fabricate silicon nano transistors for future ICs is AFM nanolithography.